Kebijakan Perubahan Kurikulum 2013 dalam Menyongsong Indonesia Emas Tahun 2045 - Imam Machali (Jurnal Pendidikan Islam, 2014)
This article is intended to express the basis of policy changes in curriculum 2013, the elements of changes, and the implications of changes in the 2013 curriculum learning system. The results show that the policy of the 2013 curriculum change is based on internal and external challenges that are faced by some Indonesian people in order to prepare for their future generations that are much more productive, creative, innovative, and effective. Curriculum policy in 2013 is intended to fulfill some existing shortcomings that are in the previous curriculum. Curriculum 2013 is compiled to develop and to strengthen attitudes, knowledge, and skills in a balanced way. The change of policy in 2013 regarding the four elements of curriculum changes are on Competency Standards (SKL), Content Standard (SI), Standard Process, and Assessment Standards. Furthermore, the learning system of curriculum policy changes in 2013 makes the impact on four issues, they are the learning models of thematic-integrated, scientific approach, active strategies, and authentic assessment.